Wellness in Whiteness Biomedicalization and the Promotion of Whiteness and Youth among Women - Mire, Amina (Routledge research in gender and society, 2019)
"This book analyses the social and ethical implications of the globalization of emerging skin-whitening and anti-ageing biotechnology. Using an intersectional theoretical framework and a content analysis methodology drawn from cultural studies, the sociology of knowledge, the history of colonial medicine and critical race theory, it examines technical reports, as well as print and online advertisements from pharmaceutical and cosmetics companies for skin-whitening products. With close attention to the promises of 'ageless beauty', 'brightened', youthful skin and solutions to 'pigmentation problems' for non-white women, the author reveals the dynamics of racialization and biomedicalization at work. A study of a significant sector of the globalized health and wellness industries - which requires the active participation of consumers in the biomedicalization of their own bodies - Wellness in Whiteness will appeal to social scientists with interests in gender, race and ethnicity, biotechnology and embodiment."